THE STUDY OF APHASIA IN MEGUMI’S CHARACTER IN THE THIRD EPISODE OF “MR.BRAIN DORAMA” - HARDIYANTI, CANTIKA PUTRI (Jurnal Ilmiah Mahasiswa FIB, 2013)
Language is one of the most important things in human’s life to express their thoughts and feelings. However, some problems dealing with language ability can happen because of language disorders, one of them is Aphasia. This study is aimed at describing (1) The symptoms of Aphasia that are found in Megumi’s character, (2) The communication gap between the interlocutor and Megumi as a patient who suffers from Aphasia, and (3) The communication strategies that are used by the interlocutor to communicate with Megumi as a patient who suffers from Aphasia.This research applied qualitative approach and document analysis in analyzing Aphasia phenomena in the subtitle and scenes of third episode of “Mr.Brain” dorama. The writer used a theory proposed by National Institute on Deafness and Communication Disorder (NIDCD, 2008) and a theory of communication gap proposed by Karten (2002) in analyzing dialogues of Megumi and the interlocutors in the movie script.The findings reveal that there are three Aphasia symptoms which refer to Wernicke’s Aphasia shown by Megumi as the Aphasia patient in the third episode of “Mr. Brain” dorama. They are having difficulties in understanding words, having the ability of speaking, and having no weakness in tactile sensor and body. She is also unable to reconnect memory bank which has an important role in gaining back her vocabularies. The writer also finds mismatched communication preferences and mistaken assumption of understanding as the factors that cause communication gap. Moreover, the therapist can avoid some gaps in order to find the appropriate treatment to heal Megumi. Furthermore, the writer figures out three communication strategies that are used in Megumi’s treatment. They are maintaining a natural conversational manner appropriate for an adult; repeating the content words and using prolongation in each word; and encouraging any type of communication, whether it is speech, gesture, pointing, or drawing. In Megumi’s case, a Japanese word game (Shiritori) becomes the best treatment to improve her vocabularies.Through this study, the writer suggests for the future researchers who are interested in exploring Aphasia to investigate other Aphasia phenomena. The future researchers can also do further investigation in the relation of communication strategies with the progression of the Aphasia patient in gaining back his or her language ability. Keywords: Aphasia, Speech Production, Symptom, Communication Gap, Communication Strategy, Megumi, “Mr. Brain Dorama”.